A Novel Shape-Memory Monofilament Suture for Minimally Invasive Thoracoscopic Cardiac Surgery. Issue 1 (February 2019) - Seguchi, Ryuta; Ishikawa, Norihiko; Tarui, Tatsuya; Horikawa, Takafumi; Ushijima, Teruaki; Watanabe, Go
Abstract : Objectives: Endoscopic knot tying can complicate or prolong minimally invasive surgical procedures. A novel shape-memory monofilament suture with a spiral tail has been developed to speed up suture fixation during minimally invasive cardiac surgery. The purpose of this study was to evaluate its usefulness and safety in minimally invasive cardiac surgery. Methods: We installed a needle with a 4–0 monofilament suture, composed of polyvinylidene difluoride and hexafluoropropylene copolymers, in an originally invented jig and heated it in an oven. By only passing through the needle and then into the spiral made at the tail of the suture, a hangman's knot was easily made. For the fundamental experiment, to evaluate the effectiveness of the novel shape-memory monofilament suture, 4 surgeons with varying thoracoscopic experience tied knots within a simulated minimally invasive setting, using both the novel shape-memory and conventional monofilament sutures. The time elapsed for knot tying and tensile strength of each knot was measured. Results: The mean knot-tying time was significantly shorter with the novel suture than with the conventional suture (108 ± 29 vs. 172 ± 42 seconds, P = 0.01). The ultimate tensile strength of each knot was 17.4 N in the novel suture and 16.5 N in the conventional suture. Conclusions: The novel shape-memory monofilament suture has great potential for reducing operative time of minimally invasive thoracoscopic surgery while retaining the strength of the knot.